2013
DOI: 10.1021/jf3044764
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Antioxidant Peptides from Jinhua Ham

Abstract: The antioxidant activities of the peptides extracted from Jinhua ham were evaluated on the basis of hydroxyl radical scavenging activity, DPPH radical scavenging activity, and Fe(2+) chelating ability. The peptide extracts exhibited great hydroxyl radical scavenging activity and DPPH radical scavenging activity as well as Fe(2+) chelating ability at the concentration of 1 mg/mL, which suggested the presence of peptides with antioxidant activity. The peptides were separated using size exclusion chromatography a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(67 citation statements)
references
References 37 publications
1
65
1
Order By: Relevance
“…Zhu, Zhang [12] reported that the peptide content of Jinhua hams was 1.16% and that these crude peptides also exhibited high antioxidant activity. In the study of Escudero, Mora [26], ACE-inhibitory activity of peptides from Spanish dry-cured ham was also investigated and an inhibition of 60.7% at 10 mg/mL was reported.…”
Section: Ace-inhibitory Activity Of Jhpmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu, Zhang [12] reported that the peptide content of Jinhua hams was 1.16% and that these crude peptides also exhibited high antioxidant activity. In the study of Escudero, Mora [26], ACE-inhibitory activity of peptides from Spanish dry-cured ham was also investigated and an inhibition of 60.7% at 10 mg/mL was reported.…”
Section: Ace-inhibitory Activity Of Jhpmentioning
confidence: 99%
“…Crude peptides extracted from Jinhua ham were proved to possess DPPH scavenging ability of 77.39% and great antioxidant activity in PC12 cell model [10,11]. Peptide with sequence of GKPNV purified from Jinhua ham has been isolated and assayed to have a great antioxidant activity [12]. However, no studies have investigated the antihypertensive abilities of Jinhua ham peptides (JHP) to date.…”
Section: Introductionmentioning
confidence: 99%
“…However, healthy cells may be damaged by the many side effects of anticancer drugs, and resistance to anticancer drugs has been observed [3]. Therefore, substantial attention is being paid to identifying anticancer drugs with high efficiency and low toxicity from natural sources [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Dry‐cured ham could experience extensive proteolysis, producing functional peptides during the long processing period (Zhang et al ., ; Zhu et al ., ). Xing et al .…”
Section: Introductionmentioning
confidence: 99%